Cardioprotection by gene therapy: A review paper on behalf of the Working Group on Drug Cardiotoxicity and Cardioprotection of the Italian Society of Cardiology. (15th July 2015) - Madonna, Rosalinda; Cadeddu, Christian; Deidda, Martino; Giricz, Zoltán; Madeddu, Clelia; Mele, Donato; Monte, Ines; Novo, Giuseppina; Pagliaro, Pasquale; Pepe, Alessia; Spallarossa, Paolo; Tocchetti, Carlo Gabriele; et al.
Abstract: Ischemic heart disease remains the leading cause of death worldwide. Ischemic pre-, post-, and remote conditionings trigger endogenous cardioprotection that renders the heart resistant to ischemic–reperfusion injury (IRI). Mimicking endogenous cardioprotection by modulating genes involved in cardioprotective signal transduction provides an opportunity to reproduce endogenous cardioprotection with better possibilities of translation into the clinical setting. Genes and signaling pathways by which conditioning maneuvers exert their effects on the heart are partially understood. This is due to the targeted approach that allowed identifying one or a few genes associated with IRI and cardioprotection. Genes critical for signaling pathways in cardioprotection include protectomiRs ( e.g., microRNA 125b*), ZAC1 transcription factor, pro-inflammatory genes such as cycloxygenase (COX)-2 and inducible nitric oxide synthase (iNOS), antioxidant enzymes such as hemoxygenase (HO)-1, extracellular and manganese superoxidase dismutases (ec-SOD and Mg-SOD), heat shock proteins (HSPs), growth factors such as insulin like growth factor (IGF)-1 and hepatocyte growth factor (HGF), antiapoptotic proteins such as Bcl-2 and Bcl-xL, pro-apoptotic proteins such as FasL, Bcl-2, Bax, caspase-3 and p53, and proangiogenic genes such as TGFbeta, sphingosine kinase 1 (SPK1), and PI3K–Akt. By identifying the gene expression profiles of IRI and ischemic conditioning, one may reveal potential gene targets responsible for cardioprotection. In this manuscript, we review the current state of the art of gene therapy in cardioprotection and propose that gene expression analysis facilitates the identification of individual genes associated with cardioprotection. We discuss signaling pathways associated with cardioprotection that can be targeted by gene therapy to achieve cardioprotection. Highlights: We review the role of gene therapy in cardioprotection. We propose that gene expression analysis may facilitate cardioprotection. We discuss signaling pathways associated with cardioprotection.